The Effect of Ease of Use and Perceived Value on User Loyalty of the DANA E-Wallet in Singkawang City with User Satisfaction as an Intervening Variable - Ghita Octavia; Muhammad Ebuziyya Alif Ramadhan (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of ease of use and perceived value on user loyalty with user satisfaction as a mediating variable in the use of the DANA e-wallet in Singkawang City. This study uses a quantitative approach with an associative method. The research population includes all DANA e-wallet users domiciled in Singkawang City, with a sample of 100 respondents determined through purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares with the assistance of SmartPLS version 3 software. Model testing includes evaluation of the outer model and inner model, which includes convergent and discriminant validity tests, the Average Variance Extracted (AVE) value, and reliability testing. Meanwhile, inner model testing was carried out through analysis of R-square values, direct effects, and indirect effects. The results show that ease of use and perceived value are able to explain the variability of user satisfaction by 73.0%, while the remaining 27.0% is influenced by other factors outside the research model. Furthermore, based on the R-square value of the user loyalty variable, it is known that the combination of ease of use, perceived value, and user satisfaction contributes 55.1%, while the other 44.9% is influenced by other variables not examined. The direct effect test results show that ease of use and perceived value have a positive and significant effect on user satisfaction, and user satisfaction, ease of use, and perceived value have a direct effect on user loyalty. In addition, the results of the indirect effect test prove that user satisfaction acts as a mediating variable in the relationship between ease of use and perceived value on the loyalty of users of the DANA e-wallet.